Entropic forces drive contraction of cytoskeletal networks. (21st March 2016) - Braun, Marcus; Lansky, Zdenek; Hilitski, Feodor; Dogic, Zvonimir; Diez, Stefan
Abstract : The cytoskeleton is a network of interconnected protein filaments, which provide a three‐dimensional scaffold for cells. Remodeling of the cytoskeleton is important for key cellular processes, such as cell motility, division, or morphogenesis. This remodeling is traditionally considered to be driven exclusively by processes consuming chemical energy, such as the dynamics of the filaments or the action of molecular motors. Here, we review two mechanisms of cytoskeletal network remodeling that are independent of the consumption of chemical energy. In both cases directed motion of overlapping filaments is driven by entropic forces, which arise from harnessing thermal energy present in solution. Entropic forces are induced either by macromolecular crowding agents or by diffusible crosslinkers confined to the regions where filaments overlap. Both mechanisms increase filament overlap length and lead to the contraction of filament networks. These force‐generating mechanisms, together with the chemical energy‐dependent mechanisms, need to be considered for the comprehensive quantitative picture of the remodeling of cytoskeletal networks in cells. Abstract : Directional sliding of overlapping filaments relative to each other is one of the key means of the remodeling of cytoskeletal filament networks. Traditionally, filament sliding is considered to be driven by molecular motors. Recent findings show that directional filament sliding can be also driven by macromolecular crowding or by non‐enzymatic diffusible filament crosslinkers confined in the filament overlaps.